Faktor Pendorong Sedekah dan Upaya Maintaning Sedekah Pada Lembaga Sosial - Mohammad Abdul Gofur; Desi Erawati (Dialogia, 2020)
Abstract: This paper aims to find out how prosocial motivation is to give charity to the community and how prosocial efforts to maintain motivation to give charity in social institutions of Darul Amin Palangka Raya, where is motivation of prosocial charity especially in Indonesia is still very weak, this is influenced by several factors.  This research was conducted qualitatively, by taking six informan this research subjects with criteria: high economy, medium economy, and low economy; and became a donor of the Darul Amin Palangka Raya. The findings in this study are two factors that determine the motivation of prosocial charity at the Darul Amin, first, internal factors such as: understanding the wisdom of giving and giving as a form of gratitude; and second, external factors such as: the inheritance of exemplary parents, the task of conveying the truth, humanity, the support of people closest to the environment, and sharing of happiness. There have been several attempts by prosocial to maintain their motivation to give to charity including remembering the messages of parents, listening to lectures both in pronunciation, social medical, reading books.الملخص: يهدف هذا البحث إلى معرفة كفية الدافعين الاجتماعيين في الصدقة وكيفية احتفاظهم بها في المؤسسة الاجتماعية دار الأمين بالنكارايا، حيث لا يزال الدافعين الاجتماعيين في الصدقة خاصة في إندونيسيا ضعيفا جدا، ويتأثر هذا بعدة عوامل. ويتم إجراء هذا البحث نوعيا من خلال أخذ ستة الأفراد من هذا البحث بالمعايير منها: الاقتصاد المرتفع، والاقتصاد المتوسط، والاقتصاد المنخفض، وأصبح متبرعا بالمؤسسة الاجتماعية دار الأمين بالنكارايا. تعتبر النتائج في هذا البحث عاملين يحددان الدافع الاجتماعي في الصدقة لدار الأمين، الأول، العوامل الداخلية منها: فهم حكمة الصدقة والصدقة شكل من أشكال الشكر. والثاني، العوامل الخارجية منها: إرث الأسوة من الوالدين، ومهمة إيصال الحقيقة، والإنسانية، ودعم الأشخاص الأقرب والبيئة، وتقاسم السعادة. هناك عدة محاولات من الدافعين الاجتماعين في الاحتفاظ بالصدقة منها تذكر رسالة الوالدين، والاستماع إلى الدعوة من المجلس والشبكة الدولية، وقراءة الكتاب عن .Abstrak: Tulisan ini bertujuan untuk mengetahui bagaimana motivasi prososial bersedekah masyarakat dan bagaimana upaya para prososial mempertahankan motivasi bersedekah di lembaga sosial Panti Asuhan Darul Amin Palangka Raya, dimana motivasi prososial bersedekah khususnya di Indonesia masih sangat lemah, hal ini dipengaruhi beberapa faktor. Penelitian ini dilakukan secara kualitatif, dengan mengambil enam orang subjek penelitian dengan yang berkriteria: berekonomi tinggi, berekonomi sedang, dan berekonomi lemah; dan menjadi donator lembaga sosial Panti Asuhan Darul Amin Palangka Raya. Temuan dalam kajian ini ada dua faktor yang menentukan motivasi prososial bersedekah di Panti Asuhan Darul Amin, pertama, faktor internal seperti: memahami hikmah bersedekah dan sebagai bentuk syukur; dan kedua, faktor eksternal seperti: warisan keteladanan orang tua, tugas sebagai penyampai kebenaran, rasa kemanusian, dukungan orang terdekat dan lingkungan, serta berbagi kebahagiaan. Ada beberapa upaya para prososial mempertahankan motivasinya untuk bersedekah diantaranya mengingat pesan orang tua, mendengarkan ceramah baik di pengajian, medis sosial, membaca buku..